2019
DOI: 10.1155/2019/5683479
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Postconditioning (IPostC) Protects Fibrotic and Cirrhotic Rat Livers after Warm Ischemia

Abstract: Background. Decreased organ function following liver resection is a major clinical issue. The practical method of ischemic postconditioning (IPostC) has been studied in heart diseases, but no data exist regarding fibrotic livers. Aims. We aimed to determine whether IPostC could protect healthy, fibrotic, and cirrhotic livers from ischemia reperfusion injury (IRI). Methods. Fibrosis was induced in male SD rats using bile duct ligation (BDL, 4 weeks), and cirrhosis was induced using thioacetamide (TAA, 18 weeks)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…There were no clear differences between the control group and the treatment group. The reason was that the preinjury and structural damage caused by CCl 4 made the histological appearance much more complex (26). Therefore, we used the modified Suzuki scores, and found that these were better at evaluating visual hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…There were no clear differences between the control group and the treatment group. The reason was that the preinjury and structural damage caused by CCl 4 made the histological appearance much more complex (26). Therefore, we used the modified Suzuki scores, and found that these were better at evaluating visual hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…BDL induced massive inflammation, oxidative stress, microvascular dysfunction, and fibrosis in the liver, and these pathological changes were accompanied by impaired diastolic, systolic, and macrovascular functions, cardiac inflammation, and oxidative stress. Schewe et al ( 112 ) induced liver fibrosis in male SD rats by BDL surgery for 4 weeks. After BDL surgery, the liver showed low fibrosis and severe bile duct proliferation, accompanied by overall parenchymal fibrosis and moderately inflammatory fibrous septum.…”
Section: Surgical Induction Methodsmentioning
confidence: 99%
“…BFKB8488A is a humanized antibody that specifically activates the FGFR1/β-Klotho complex (112). In phase 2 clinical trial consisting of NAFLD patients, 12 weeks of administration of BFKB8488A diminished liver fat, serum TG and pro-C3 while increasing adiponectin and HDL (13,105,112).…”
Section: Fgf As a Drugmentioning
confidence: 99%